The Concept of God, the Origin of the World, and the Image of the Human in the World Religions
VIII, 161 p.
Keywords: All religions make statements about God or the Absolute and about "the beginning": about the beginning of the world and the beginning and nature of the human person. Propositions about God, the human person, and the world, statements about God's eternity or process of becoming, about the status and nature of the human person as the "image of God", and about the beginning of the world are woven into "religious speculations about the beginning". The theology, anthropology, and cosmology of the world religions determine the image of the human person and the image of the world in the world cultures shaped by the different religions. They stand in a tense relationship with the anthropologies and cosmologies of modern science, which in turn challenge the religions to deepen their image of the human person. With this volume leading thinkers of Hinduism, Buddhism, Judaism, Christianity, and Islam provide the reader with a first-hand source for understanding the five world religions and their teaching about God, the human person, and the origin of the world.